Critical analysis of diagnostic criteria (ICHD-3 beta) about migraine in childhood and adolescence - Ferreira Lima, Marcia Maria [UNESP]; Bazan, Rodrigo [UNESP]; Martin, Luis Cuadrado [UNESP]; Martins, Antonio Sergio [UNESP]; Luvizutto, Gustavo Jose [UNESP]; Gomes Garcia Betting, Luiz Eduardo [UNESP]; Zanini, Marco Antonio [UNESP] (Assoc Arquivos Neuro- Psiquiatria, 2015)
Objective: The objective of this study was to prospectively evaluate the International Classification of Headache Disorders I (ICHD-I) diagnostic criteria for migraine in children and adolescents. Methods: 150 pain diaries were analyzed during an initial consultation. The duration of migraine headache attacks were divided into 2 groups: Group I, for attacks lasting > 2 hours, and Group II, for attacks lasting < 2 hours. The two groups were statistically compared using Fisher's exact test (p < 0.05). Results: In this study, 51(34%) subjects were male and 99 (66%) were female, aged 7-15 years. Fisher's exact test demonstrated that the ICHD-3 beta had a 58% sensitivity for Group I diagnoses and a 94% sensitivity for Group II diagnoses (p < 0.001). Conclusion: The current ICHD-3 beta classification improves and advances migraine diagnosis in children and adolescents; however, more research is needed to identify additional characteristics of headache in this age group.
Keywords: headache; diagnostic criteria; childhood; adolescence